Militaries, finance, and (in)security - Emily Gilbert (Finance and Society, 2017)
This essay points to some of the ways that militaries are focused on money and economics, and addresses what this means for understanding the entanglements of security and finance. We cannot think about security in the contemporary moment without also thinking about militaries and war, and it is only by addressing how military power engages money and finance that can we better understand how insecurity is enacted.
Keywords: 300